The association between physical outputs and match outcome across different playing styles for a professional second-tier football team across two complete seasons - Mason, L.; Panayi, S.; Wright, J.; Bruce-Low, S. (The Journal of Sports Medicine and Physical Fitness, 2024)
BACKGROUND: Elite-level football requires an array of physical, technical, psychological, and tactical skills. The aim of this study was to measure the association between physical outputs (distance, decelerations, accelerations) and the match outcome (win, draw, lose) in professional football. This research also examined whether the same association is influenced if a team adopts a possession or transition-based playing style.